Case Report: Usefulness of Drip Infusion Cholangiography With Computed Tomography for the Diagnosis of Biloma in a Dog - Tamura, Masahiro; Ohta, Hiroshi; Hasegawa, Nene; Hosoya, Kenji; Takiguchi, Mitsuyoshi (Frontiers in Veterinary Science, 2022)
Bilomas are an encapsulated collection of bile outside or inside the biliary tract within the abdominal cavity. For diagnostic and therapeutic approaches, it is important to identify the origin of bile leaks from the biliary tract. This case report describes the usefulness of drip infusion cholangiography with computed tomography (DIC-CT) for detecting the site of bile leakage in a dog with biloma. A 10-year-old, castrated male Pomeranian was referred to our department for gastrointestinal signs. Abdominal ultrasonography detected gallbladder mucocele with localized fluid accumulation around the right division of the liver. Although the accumulation of fluid indicated bile peritonitis, plasma total bilirubin was within normal limits. The DIC-CT with meglumine iotroxate showed two well-defined large fluid collections: one between right medial and lateral lobe and the other between the right lateral lobe and caudate process of caudate lobe. Three-dimensional DIC-CT views that the former was enhanced by the contrast agent and that it communicated with an intrahepatic bile duct of the right lateral lobe. Moreover, the DIC-CT images confirmed communication with each fluid collections. After 6 days of hospitalization, a decrease in the amount of accumulated fluid was confirmed, after which cholecystectomy was performed. The dog was discharged from the hospital without complications. No signs of bile leakage were observed on follow-up imaging on postoperative day 10. This has been the first report to show that DIC-CT can be useful for determining the origin of bile leakage in dogs with bilomas.